Pulmonary Targeting of Inhalable Moxifloxacin Microspheres for Effective Management of Tuberculosis - Bhavya Vishwa; Afrasim Moin; D. V. Gowda; Syed M. D. Rizvi; Wael A. H. Hegazy; Amr S. Abu Lila; El-Sayed Khafagy; Ahmed N. Allam (MDPI AG, 2021)
In the present study, the objective was to attain a localized lung delivery of an anti-tubercular fluoroquinolone, moxifloxacin (MXF), targeting the alveolar macrophages through a non-invasive pulmonary route using inhalable microspheres as a dry powder inhaler approach. MXF-loaded poly (lactic-co-glycolic acid) (PLGA) microspheres (MXF-PLGA-MSs) were fabricated by solvent evaporation technique and optimized by using a central composite statistical design. The morphology and particle size, as well as the flowability of the optimized microspheres, were characterized. In addition, the aerosolization performance of the optimized formula was inspected using an Andersen cascade impactor. Furthermore, in vivo fate following intrapulmonary administration of the optimized formula was evaluated. The optimized MXF-PLGA-MSs were spherical in shape with a particle size of 3.16 µm, drug loading of 21.98% and entrapment efficiency of 78.0%. The optimized formula showed a mass median aerodynamic diameter (MMAD) of 2.85 ± 1.04 µm with a favorable fine particle fraction of 72.77 ± 1.73%, suggesting that the powders were suitable for inhalation. Most importantly, in vivo studies revealed that optimized MXF-PLGA-MSs preferentially accumulated in lung tissue as manifested by a two-fold increase in the area under the curve AUC0-24h, compared to plain drug. In addition, optimized MXF-PLGA-MS sustained drug residence in the lung for up to 24 h following inhalation, compared to plain drug. In conclusion, inhalable microspheres of MXF could be a promising therapeutic approach that might aid in the effective eradiation of tuberculosis along with improving patient adherence to the treatment.